Valproic Acid-Induced Hepatotoxicity and the Protective Role of Thiol Reductants - Nahid Najafi; Akram Jamshidzadeh; Hamideh Fallahzadeh; Mahmoud Omidi; Narges Abdoli; Asma Najibi; Negar Azarpira; Reza Heidari; Hossein Niknahad (Shiraz University of Medical Sciences, 2017)
Valproic acid (VPA) is a widely administered drug against epilepsy and several other neurological disorders. On the other hand, liver injury is a deleterious side effect associated with VPA. Oxidative stress seems to play a critical role in VPA-induced hepatotoxicity. The current investigation was designed to evaluate if N-acetylcysteine (NAC) and dithiothreitol (DTT) as thiol reducing agents have any protective effects against VPA-induced liver injury. Isolated rat hepatocytes (in vitro) were exposed to increasing concentrations of VPA (25, 50, 100, 150, and 250 µM) and markers of cytotoxicity were evaluated. Furthermore, animals received VPA (250 and 500 mg/kg, i.p for 15 consecutive days) (in vivo) and markers of liver injury were monitored. It was found that 250 µM of VPA caused marked cytotoxicity toward isolated hepatocytes as judged by trypan blue exclusion test. Moreover, markers of oxidative stress including glutathione depletion and lipid peroxidation were detected in VPA-treated hepatocytes. On the other hand, VPA caused a significant increase in plasma markers of hepatotoxicity in drug-treated group. Liver histopathological changes and markers of oxidative stress were also detected in VPA-treated animals. It was found that administration of NAC (1 mM), and DTT (1 mM) significantly alleviated VPA-induced cytotoxicity (In vitro). NAC (250 and 500 mg/kg) and DTT (15 and 30 mg/kg) also significantly mitigated VPA hepatotoxicity (In vivo). The data obtained from the current investigation indicate potential therapeutic properties of thiol reductants against VPA-induced liver injury.